2023
DOI: 10.1159/000527711
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial COVID-19: A Nationwide Spanish Study

Abstract: <b><i>Introduction:</i></b> SARS-CoV-2 is a highly contagious virus, and despite professionals’ best efforts, nosocomial COVID-19 (NC) infections have been reported. This work aimed to describe differences in symptoms and outcomes between patients with NC and community-acquired COVID-19 (CAC) and to identify risk factors for severe outcomes among NC patients. <b><i>Methods:</i></b> This is a nationwide, retrospective, multicenter, observational study that analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
1
7
1
1
Order By: Relevance
“…Nosocomial and community-acquired COVID-19 have been frequently compared in the literature. In our study, patients with nosocomial COVID-19 were older and had a longer hospital stay than patients with community-acquired COVID-19 as it was previously demonstrated in three other studies [4] , [28] , [29] . We identified a higher mortality in patients with nosocomial (36%) than in those with community-acquired COVID-19 (21%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nosocomial and community-acquired COVID-19 have been frequently compared in the literature. In our study, patients with nosocomial COVID-19 were older and had a longer hospital stay than patients with community-acquired COVID-19 as it was previously demonstrated in three other studies [4] , [28] , [29] . We identified a higher mortality in patients with nosocomial (36%) than in those with community-acquired COVID-19 (21%).…”
Section: Discussionsupporting
confidence: 81%
“…An observational study had similar results as ours for mortality of nosocomial cases (32%) but they identified a higher proportion of admissions to the ICU for patients with nosocomial compared with those with community-acquired COVID-19 [4] . Finally, we did not identify any difference regarding gender as found in the literature [28] , [29] , [32] .…”
Section: Discussioncontrasting
confidence: 50%
“…Previous studies investigating nosocomial COVID-19 were largely performed before the availability of COVID-19 vaccination and effective antiviral therapies. [2][3][4][5] Reported rates of nosocomial COVID-19 cases vary between 5% and 17%. 4,5 The mortality rate of nosocomial COVID-19 in these studies ranged from 27% to 41%.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Reported rates of nosocomial COVID-19 cases vary between 5% and 17%. 4,5 The mortality rate of nosocomial COVID-19 in these studies ranged from 27% to 41%. In the COPE-Nosocomial Study (COVID in Older People), conducted in early 2020, nosocomial COVID-19 infection was associated with a similar mortality rate compared with communityacquired infections, 2 whereas, in others, patients with nosocomial COVID-19 did worse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation